Dorset Fire Authority Wiltshire and Swindon Fire Authority : Consultation on locally -led proposals to create a combined fire and rescue authority for Dorset and Wiltshire.: Consultation on locally -led proposals to create a combined fire and rescue authority for Dorset and Wiltshire. (December 2014) - Great Britain., Department for Communities and Local Government,
No abstract available